Giant cell tumor of the bone of maxillary sinus: A rare uncommon manifestation implicated in a new mosaic of disorders? (Research, Society and Development, 2022)
The goal is to show a rare case of Giant Cell Tumor of Bone in the maxillary sinus implicated in a process coincidentally or casually with another type of lesion primarily developed. A 33-year-old male patient attended a surgical service, presenting swelling, obstruction and firm mass externalizing through the right nostril and perceived during 6 months. During the anamnesis, the patient stated to been underwent an incisional biopsy 4 years ago of a tumor with histopathological diagnosis of the Nasal Paraganglioma, however the immunohistochemical study was negative for this tumor. During the Computed Tomography evaluate was observed a hyperdense mass occupying the entire maxillary sinus. In the Nuclear Magnetic Resonance evaluation, it was showed a hypersignal image in the entire maxillary sinus, invading the nasal cavity and portion of skull base. A bone window was performed in the right maxillary sinus and excisional biopsy was made. In the new histopathological examination, the diagnose was consistent with Giant Cell Tumor of Bone, being observed a large number of multinucleated giant cells, some with disorganized nuclei and others similar to Touton giant cells. A large proliferation of xanthomatous-looking cells was also observed without features of malignity. At the 3-year follow-up, the patient reported no complications such as facial paralysis, infection, relapse or spread. The association between lesions occurring in the same location requires further study, possibly implicated in a new model of clinical, microscopic, and genetic disorders. Thus, masses originating from chronic inflammatory tissue may have the potential to transform into GCTB?